Pulse-Driven Paired Electrosynthesis of Formamide via Redox-Tuned Intermediate Management - Xiang-Da Zhang; Pengsong Li; Yong Wang; Ganwen Zhang; Yuqing Hou; Xihua Wang; Congyang Wang; Xinchen Kang; Huizhen Liu; Yi Xu; Qinggong Zhu; Buxing Han (Journal of the American Chemical Society, 2026)
Abstract Renewable electricity-driven electrocatalytic systems hold promise for the sustainable formamide (HCONH2) synthesis. However, a major bottleneck remains the low Faradaic efficiency (FE) and overall electron utilization inherent to current unipolar C–N coupling strategies, where substantial electron consumption at the counter electrode severely limits system efficiency. Here, we propose a redox-tuned paradigm (Ared+ Boxi→ C) through a pulsed paired electrosynthesis strategy. Using an atomically ordered CuPd catalyst with CH3OH and NO2– as feedstocks in an undivided cell, HCONH2 is simultaneously produced at both electrodes under optimized pulse conditions with alternating change in potential periodically (Ea = 1.3 V, ta = 10 s; Ec = −0.7 V, tc = 10 s). This system achieves an FE of 85.6% for HCONH2 at a current density of 81.5 mA cm–2, with a yield of 263.3 μmol·h–1·cm–2. The FE is higher than those reported to date. Mechanism studies reveal that pulsed operation creates a periodically switching cathode/anode environment. This enables the ordered CuPd catalyst to function sequentially as a reduction site (converting NO2– to *NH3) during cathodic pulses and as a co-oxidation site (converting *NH3 to *NH2 along with CH3OH to *HCOH) during anodic pulses, thereby driving efficient C–N bond coupling to form HCONH2. Techno-economic analysis further confirmed the significant industrial potential of this strategy in the future renewable energy market.